MACROBENTHIC COMMUNITY STRUCTURES OF THE OFFSHORE AREA OF MIMIKA DISTRICT, PAPUA - Kastoro, Woro W.; Amiruddin, -; Azis, A.; Aswandi, I.; Al Hakim, I.; Lala, Deky; Setyadi, Gesang (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
The study on macrobenthic community structures was carried out in the offshore area of Mimika district, Papua in 2005. Steep mountain slopes and some of the highest rainfall rates in the world, have generated tremendous sediment loads that have settled in the alluvial plain and been carried out into the estuaries and the Arafura Sea, creating a massive area of deposited natural sediments. The objective of this study was to determine how the benthic community structures of the offshore area (Arafura Sea) changes as a result of environmental conditions. To accomplish the objective, samples were collected from 40 stations which were divided into 4 contours (layers) of water depth, i.e. 5, 10, 20 and 40 m. Stations of each contour depth were established perpendicular to the river mouths of Mimika district. The results showed the bottom sediments were mostly silt-clay fractions except the deeper area (40 m depth) which was dominated by very fine sand fraction. Diversity indices, Shannon index (H) and Pielous evenness (e) index ranged from 1.00-3.50 and 0.20-0.92 respectively. These indices tended to increase in the deeper areas. In total 266 species of macro-benthos were collected from the study area. Contrary to this, the densities tended to decrease in deeper areas with the range of 195.00 â 4110.00 individualsm-2. Polychaetes was the the dominant group, 50.80 â 71.80 % of the total family of macrobenthos. Among the macrobenthos, there were some families and group of taxa which had high densities such as Sipuncula, Nemertea and crustaceans including Ampeliscidae, Gammaridae and Israeidae. Among the polychaete group were the families Spionidae, Owenidae, Sternaspidae, Cossuridae, Capitellidae, Nephtyidae, Magelonidae and Pilargidae. Based on density, macrobenthos of the study area shows relatively high production. High rates of sedimentation of Ajkwa estuary does not influence the structure of macrobenthic communities in the offshore area.